Exploring the genetic correlations of antisocial behaviour and life history traits. Issue 6 (November 2018) - Tielbeek, Jorim J.; Barnes, J.C.; Popma, Arne; Polderman, Tinca J.C.; Lee, James J.; Perry, John R.B.; Posthuma, Danielle; Boutwell, Brian B.
Summary: Prior evolutionary theory provided reason to suspect that measures of development and reproduction would be correlated with antisocial behaviours in human and non-human species. Behavioural genetics has revealed that most quantitative traits are heritable, suggesting that these phenotypic correlations may share genetic aetiologies. We use genome-wide association study data to estimate the genetic correlations between various measures of reproductive development ( N = 52 776–318 863) and antisocial behaviour ( N = 31 968). Our genetic correlation analyses demonstrate that alleles associated with higher reproductive output (number of children ever born, r g = 0.50, P = 0.0065) were positively correlated with alleles associated with antisocial behaviour, whereas alleles associated with more delayed reproductive onset (age at first birth, r g = −0.64, P = 0.0008) were negatively associated with alleles linked to antisocial behaviour. Ultimately, these findings coalesce with evolutionary theories suggesting that increased antisocial behaviours may partly represent a faster life history approach, which may be significantly calibrated by genes. Declaration of interest: None.